One Health ethics: The need for policy before research and action - Cooper, Tarni L.; Kirino, Y.; Alonso, Silvia; Lindahl, Johanna F.; Nga T.H. Le; Grace, Delia (International Livestock Research Institute, 2016)
One Health implies a strong emphasis on ethics, recognising the interdependent relationships of humans, animals and the environment. We argue that the universal ethical principles for human-subject research, presented in the Belmont report as Respect for Persons, Beneficence and Justice, should be applied to custodians of animals and the environment. Drawing on published and unpublished research, we highlight the challenges and opportunities of this approach in practice and policy. Respect for Persons is demonstrated through informed consent. We describe the high rate of consent received in livestock research projects, raising questions around legitimacy, and outline a study to improve comprehension and engagement in the informed consent process for livestock keepers. Beneficence dictates that benefits to research participants are maximized. We outline how a long-term impact assessment was designed with intrinsic value for farmers, using participatory photography. Additionally, we describe efforts towards non-maleficence through providing participants with research board contacts. We provide new data on low contact-rates and discuss possible causes. Justice requires that research risks and benefits are distributed equally. We show how the requirement to sign written consent forms may preclude those working in informal livestock markets from participating in, and therefore sharing risks and benefits of research projects.